SONG AS MEDIA IN OBTAINING INPUT AND IMPROVING LISTENING COMPREHENSION SKILL ON STUDENTS OF EDUCATION OF BAHASA INDONESIA STUDY PROGRAM - ASTARINI, SEPTIAN DWI (Jurnal Ilmiah Mahasiswa FIB, 2013)
English is a language which is used to communicate among people around the world. Language can be obtained by acquiring and learning. In Indonesia, English is classified as foreign language so that the people need to learn it. Learning language can use some materials, for example song. The writer conducted a study about language learning which deals with the input, in form of vocabulary and meaning, from songs. In conducting the research, the writer used participants to do a test that can measure the kinds of input the participant achieved. There are two problems analyzed by the writer, namely: (1) The positive and negative evidence of words, phrases or sentences that learners can catch after listening to the songs and (2) How the learners grasp the meaning of the song when retelling the content of the songs.This study uses qualitative approach since the writer would describe the result of the test. In addition, case study involves because the participants are under one institution, that is Faculty of Cultural Studies, Universitas Brawijaya. There are three participants that were involved in this study. They are students from Education of Bahasa Indonesia Study Pogram.This study reveals that each participant has different result of gaining positive and negative evidence of vocabulary and interpreting the meaning. The result of gaining positive evidence of vocabulary presents that, for song I, the participant I gained 9 positive evidences and 3 negative evidences, participant II gathered 5 positive evidences and I negative evidence, and participant III achieved 13 positive evidences and 2 negative evidences. Next, for song II, participant I collected 19 positive evidences and 10 negative evidences, participant II found 13 positive evidences and 6 negative evidences and participant III gained 28 positive evidences and I negative evidence. In term of meaning, participant I had interpretation which is not really close to the original meaning, participant II had close meaning interpretation to original meaning for song I while participant III had close interpretation to original meaning for song II. In sum, the last participant shows that she has the highest number of collecting positive evidence and has closer meaning to the original meaning for song II while the meaning of the song I is close to the participant II.The writer suggests the next researcher who wants to investigate the use of media as material in language learning employ different ages of participants and focus on different aspect. The use of other media is also suggested for the next researcher to investigate the input.  Keywords: song, language learning, input, positive evidence, negative evidence